A QOS-based service retrieval methodology for the digital ecosystems - Dong, Hai; Hussain, Farookh Khadeer; Chang, Elizabeth (Inderscience Enterprises Ltd, 2009)
The emergence of the World Wide Web and its influence on the field of industry, commerce, healthcare etc. has led to an innovative, dynamic, open, collaborative and interactive environment - Digital Ecosystems. Whereas service plays an important role in the Digital Ecosystems, there is no technology available to retrieve the heterogeneous and geographically dispersed services. Additionally, no methodology has been proposed in the literature that can distinguish or rank the services based on the Quality of Services(QoS). In order to address these issues, we propose a semantic service retrieval engine which incorporates a novel semantic QoS evaluation methodology. The salient feature of this methodology, that sets it apart from any other QoS evaluation methodologies, is that the evaluation of the service and the subsequent quantification of QoS is a combination of subjective QoS measures and objective QoS measures. Another salient feature of our proposed methodology is that it enables the domain-specific ranking of services. Finally, an online prototype is implemented to evaluate our methodology, the results of which are discussed in this paper.